Prototype Sistem Informasi Peminjaman Laboratorium Komputer Berbasis Android: Penelitian - Siti Hartinah; Rizky Andhika Surya; Panggah Widiandana; Muhammad Immawan Aulia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The process of borrowing computer laboratories in most educational institutions is still done manually using notebooks or borrowing sheets. This causes various obstacles such as schedule duplication, data loss, and difficulty in monitoring laboratory usage. This study aims to design and build a prototype of a computer laboratory borrowing information system using Android that can facilitate the management of borrowing schedules effectively and efficiently. The method used is the Software Development Life Cycle (SDLC) with the Waterfall model with the stages of requirements analysis, implementation, system design and testing. The result of this study is an Android-based application that can be used to apply for laboratory borrowing, display the borrowing schedule, and provide notification of borrowing status to users. For testing using Black Box shows that the system runs according to the expected use. Thus, this application can be an effective solution to increase administrative efficiency and transparency in the computer laboratory borrowing process